Innovative solutions in container transport - Zielaskiewicz Henryk (Przegląd Komunikacyjny)
The article presents a historical perspective on the development of transport technology, i.e. a container. It was indicated what solutions are currently used on terminals in order to shorten the service time of intermodal units and ensure an increase in the efficiency of handling operations. Intelligent containers are presented, which are equipped with numerous sensors, which include can follow the route of the container. The author outlined what activities are currently carried out by governmental and international organizations to ensure cargo safety during transport operations. The directions of changes in the design of containers and IT support systems have been signaled, and how the logistics industry reacts and should proceed in the era of the spread of the coronavirus in the event that many companies' strategies will be revised with new consumer behavior. Keywords: Intermodal transport; Intelligent containers; Information systems; Coronovirus CoVid